Structural Behavior of Continuous Steel-Reactive Powder Concrete Composiate Beams Under Repeated Loads - Yassien Dakhil, Rasha; B. Dawood, Mustafa (International Journal of Engineering and Technology, 2018)
A study for the continuous composite steel-reactive powder concrete beams under repeated loads were executed experimentally and analytically. In the experimental part, six continuous composite sections were constructed as test beams. "The‘“decks slab concretes"was connected tos steel I-beams by headed steel studs welded to the top flanges“ofs“thes‘‘steel I-beams.“T,he dimensions“ of “the“ deck slab is (2200×250×80mm), while the type of I-beam is (IPE 140) with length of (2200mm). For the present work, the experimental work includes also examining the shear in the links by creating two models (push out) and tested to determine the properties and behavior of the studs. The behavior of the studs were conducted by"getting load-slip curves. In the part of the,oretical,‘‘.tested beams.was numericallysmodeled then analyzed using thesfinite element method.‘“Thes“numerical models were carried out in three dimensionss bys“the software package (ANSYS 16.1). Verifi,cationsof thesnumericalsresults“was donesbyscompari,ngs thems with the experimentals results. “Thesresultssof thesfiniteselementsanalysissshowed good agreements‘with the results ofsthe experimental tests. The maximumsandsminimum difference‘‘in ultimate loa,ds for beams‘‘ were (5.85% and 1.33%) respectively.  The results show that stiffenerssof beamssandsstrengthening with CFRP shall increase the ultimate load capacity‘and affects on‘‘mode of failure“ of theses beams.‘